Pengaruh penggunaan uang elektronik terhadap perputaran uang di Indonesia - Wulandari, Selatri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
This study aims to analyze the effect of the use of electronic money which includes the amount of electronic money in circulation, electronic money transactions, and inflation on velocity of money in Indonesia. The analytical method used is multiple linear regression analysis with Eviews 10 program. This research is descriptive quantitative. The data used are secondary data obtained from Bank Indonesia and Badan Pusat Statistik. The results of this study obtained the regression coefficient of the variable amount of electronic money in circulation -1.800553 with a significant level of 0.0413, it can be concluded that the amount of electronic money in circulation has a negative and significant effect on velocity of money. The regression coefficient value of the electronic money transaction variable is 1.145675 with a significant level of 0.0455 with a significant level of 0.0455, it can be concluded that electronic money transactions have a positive effect on the velocity of money. While the value of the inflation coefficient is 1.497271 with a significant level of 0.0036, it can be concluded that inflation has a positive and significant effect on the velocity of money.